Islamic Pop Culture and the Commodification of Religion in Muslim Fashion Products on Instagram - Hakim, Latifa Dinar Rahmani; Novitasari, Salwa Aulia; Andiani, Paramita (Westscience Press, 2025)
This study investigates the intersection between Islamic popular culture and the commodification of religion through Muslim fashion products on Instagram. Employing a qualitative descriptive approach, data were collected through in-depth interviews with three key informants: a Muslim fashion influencer, a brand owner, and a consumer of Islamic fashion. Thematic analysis was used to explore how Islamic values are represented, negotiated, and commercialized within digital fashion culture. The findings reveal that Instagram serves as a hybrid space where faith and consumerism coexist, allowing Islamic symbols such as the hijab, modest wear, and Quranic motifs to function simultaneously as expressions of piety and as marketable commodities. Influencers and brands strategically use religious narratives to establish authenticity and attract audiences seeking both spiritual meaning and lifestyle identity. Meanwhile, consumers engage with these products as markers of belonging and moral expression, despite recognizing the risk of superficial religiosity. The study concludes that Muslim fashion on Instagram exemplifies the transformation of religion into a digital commodity—where spiritual values are aestheticized, marketed, and consumed in alignment with contemporary capitalist and media logics.